2019
DOI: 10.3389/fpsyg.2019.00306
|View full text |Cite
|
Sign up to set email alerts
|

Good Relationships, Good Performance: The Mediating Role of Psychological Capital – A Three-Wave Study Among Students

Abstract: Academic Psychological Capital, or PsyCap, – a set of positive psychological resources encompassing hope, efficacy, resilience, and optimism – has begun to gain attention in academia, showing positive relationships with desirable academic outcomes. However, studies in the field have paid limited attention to the social factors that may increase PsyCap and therefore may lead to positive outcomes. In the present study, we examine whether academic PsyCap mediates between teacher-student relationships and academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 36 publications
6
34
0
2
Order By: Relevance
“…For students, they may also run formal training to explain the conceptual mean-ing of self-regulated learning, its relationship with academic achievement (Zusho, 2017), and those personal and contextual factors which can help them to achieve highly efficient self-regulated learning (Zhu & Mok, 2018). Also, institutions can organize intervention programs for both teachers and students to develop their psychological capital (Carmona-Halty et al, 2019;Luthans et al, 2012). Previous research showed improvement in psychological capital after specific training and emphasized its visible, long-term effects (Dello Russo & Stoykova, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For students, they may also run formal training to explain the conceptual mean-ing of self-regulated learning, its relationship with academic achievement (Zusho, 2017), and those personal and contextual factors which can help them to achieve highly efficient self-regulated learning (Zhu & Mok, 2018). Also, institutions can organize intervention programs for both teachers and students to develop their psychological capital (Carmona-Halty et al, 2019;Luthans et al, 2012). Previous research showed improvement in psychological capital after specific training and emphasized its visible, long-term effects (Dello Russo & Stoykova, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The personal variables refer to students' psychological needs (i.e., autonomy, competence, and relatedness), which can be satisfied in relation to other contextual variables (e.g., teacher support or learning environment), and to students' psychological capital. As a newly proposed construct, students' psychological capital represents a set of malleable personal resources consisting of self-efficacy, hope, optimism, and resilience (Carmona-Halty, Schaufeli, & Salanova, 2019). It is considered a valuable individual resource for the effectiveness of learning, influencing students' readiness and desire to learn and to transfer learning (Combs, Luthans, & Griffith, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicated that supervisors showing similar preferences, personality traits, living backgrounds (including age, gender, race, education, seniority), and work modes with their subordinates had higher interpersonal attraction for both parties, resulting in greater interaction frequency and higher subordinate job satisfaction [20]. Carmona-Halty et al [27] discovered that operators with consistent work values with the supervisor had higher satisfaction and organizational commitment; therefore, they were more willing to commit to and concentrate on the organization. Furthermore, the interaction of supervisor and subordinate time-structuring preferences affected the subordinate's opinions regarding the job.…”
Section: Polychronicity Fit and Well-beingmentioning
confidence: 99%
“…In relation to the COR, the resources related to the psychological well-being of employees at work are nothing more than the combination of personal resources, such as hope (ability to assume the best persevering position on the objectives), effectiveness (competence to trust is their own skills), resilience (ability to overcome obstacles) and optimism (positive state facing the future), among others [41].…”
Section: Health From the Organizational Levelmentioning
confidence: 99%